Supplementary material from "Humpback whale song complexity and evolution on a North-western Pacific breeding ground: Okinawa, Japan" ... - Marwood, Eleanor M.; Eichenberger, Franca; Kobayashi, Nozomi; Okabe, Haruna; Ozawa, Sachie; Rendell, Luke; Garland, Ellen (The Royal Society, 2025)
Male humpback whales (Megaptera novaeangliae) sing a slowly evolving, sexually selected song display socially learnt from conspecifics. Within an ocean basin, song similarity between breeding populations can reveal the degree of connectivity among them. In the North-western Pacific Ocean, there is a paucity of information on song dynamics and linkages across the ocean basin. Here, we quantified fine-scale song evolution in whales near Okinawa, Japan, using similarity indices (Levenshtein Distance and Dice’s similarity) and song complexity measures to investigate three consecutive years (2011-2013) of song dynamics on this breeding ground. Matched song themes revealed minimal evolution between 2011 and 2012, while the 2013 song was more distinct, as singers sung both new and evolved versions of themes. This was mirrored by the song complexity scores which decreased and then increased over time. Qualitative comparisons of Okinawa song themes to other published North Pacific breeding ground song revealed many ...